A Comparative Study Of Grade 6 Science Students ’ Academic Achievement Under Teacher-Centered Learning Method And Inquiry -Based Learning Method At Panchasap School, Bangkok, Thailand - Gorowara, Shriya; Lynch, Richard (Scholar: Human Sciences, 2019)
The purpose of this study was to compare grade 6 science students’ academic achievement under two different teaching methods at Panchasap School, Bangkok, Thailand. The two methods were teacher-centered learning method and inquiry-based learning method. The research included five objectives. Objective one was to determine the students’ academic achievement under teacher-centered learning method in pre-test and post-test. Objective two was to determine if there was a significant difference between pre-test and post-test under teacher-centered method. Objective three was to determine students’ academic achievement under inquiry-based learning method in pre-test and post-test. Objective four was to determine if there was a significant difference between pre-test and post-test under inquiry-based learning method. Objective five was to determine if there was a significant difference in academic achievement in science between teacher-centered learning method and inquiry-based learning method. Two groups of Grade 6 students at Panchasap School, Bangkok, Thailand were used for this research study. The sample size of this study was 83 students where 42 students were under the teachercentered learning method and 41 students were under the inquiry-based learning method. The data were collected by using a pre-posttest. The pre-post test scores were analyzed by means, standard deviations, paired samples t-test and an independent samples t-test (two-tailed). The findings of the study indicated a significant difference between teacher-centered learning method and inquiry-based learning method at a significance level of .05. Students achieved higher when exposed to inquiry-based learning method.